UJI AKTIVITAS ANTIOKSIDAN FRAKSI N-HEKSAN DAUN AFRIKA (Vernonia amygdalina Del.) DENGAN METODE DPPH - Nurul Fatimah; Reksi Sundu (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Free radicals and reactive species are widely believed to contribute to the development of several diseases by causing oxidative stress and eventually oxidative. Vernonia amygdalina (Astereacea) is a small shrub or tree between 1 and 5m high growing throughout tropical Africa. Plants are generally known as bitter leaves is well cultivated and is a general market for merchandise in several countries. The purpose of this study was to determine the antioxidant activity of hexane fraction from ethanol extract od Frican leaves (Vernonia amygdalina Del.). The method used in this study was the DPPH (1,1-Diphenil-2-Picrylhydrazyl) method. The result of phytochemical screening showed that ethanolic extract of African leaves contained a composition of secondary metabolites of alkaloids, flavonoids, tannins, steroids/triterpenoids and saponins. The antioxidant activity of the extract of n-hexane fraction was classified as very weak with an IC50 value of 317.98 ppm.